A method and apparatus for inspecting large flat composite parts by using the Infrared LST technique (Fracture and Structural Integrity, 2022)
The principle of Line Scan Thermography (LST) was used to develop a self-propelled infrared thermographic nondestructive testing device for the inspection of large, relatively flat composite aerospace parts, such as aircraft wings. The design of the unit allowed the suppression of noise from reflected radiation. The new equipment, using the LST method, provided defect detectability similar to that achieved with a classic, static, flash heating procedure, but with a higher rate of testing. Also, the line heating principle ensured more uniform thermal patterns, and the proper choice of scan speed and field of view allows the selection of optimal time delays and the creation of maps of defects at different depths. Defect characterization efficiency was improved by using a trained neural network.
Keywords: Infrared Thermography; Line Scan Thermography; Composite Part; Defect Characterization; Neural Network